The Intersection of Quranic Studies and Modern Technology: A Bibliometric Analysis of Academic Publications from 2000 to 2024 - Andri Nirwana AN; Mahmudulhassan Mahmudulhassan; Mohamad Ali; Muthoifin Muthoifin; Waston Waston; Abdul Rahman Bin S. Senathirajah (Qubahan Academic Journal)
The study aims to examine patterns, subjects, and developments in scholarly works concerning Quranic studies and contemporary technology between the years 2000 and 2024. A thorough bibliometric analysis was used in the study, utilizing information from 1,225 publications from 668 sources that were indexed in Scopus. The information was gathered using keywords like “Quran,” “technology,” “computer,” “internet,” “digital,” and “science.” R/R-Studio was used for document and citation analysis, VOSviewer was used for network visualizations, and Microsoft Excel was used for data administration. The findings show noteworthy trends in the theme groupings, authorship patterns, and annual publishing rates. With an average of 5.081 citations per document and an average document age of 6.94 years, the study indicated an annual growth rate of 9.42%. 2,708 authors in all made contributions to the topic, with 10.45% of them collaborating internationally. Important phrases like “Quran,” "ontology,” and “engineering education” became crucial to narrowly targeted study projects. Leading contributors were found to be Malaysia, Indonesia, and Turkey, with research activity peaking between 2015 and 2022. The study provides insightful suggestions for future research possibilities while highlighting the transnational and collaborative nature of present Quranic studies and modern technology research. Future research should focus on enhancing multidisciplinary collaboration and leveraging advanced visualization tools to further refine research focus and effectiveness. These results offer important new perspectives on resource allocation in this dynamic field for academics and policymakers.